GAMBARAN KEJADIAN PREEKLAMSIA DENGAN SECTIO CAESAREA DI RUMAH SAKIT UMUM DAERAH KOTA KENDARI - Ester Kandek; Dian Pratiwi; Sri Surya Ibrahim; Devasmita Devasmita; Ramadhan Tosepu; Devi Savitri Effendy; Sri Susanty (NHM PRESS, 2023)
The incidence of preeclampsia in Indonesia is the main cause of maternal death with a range of 15-25%. This surgery is done by cutting by opening the abdominal wall and uterus to remove the fetus in the mother's womb. To find out the description of the incidence of severe preeclampsia and sectio caesarea (SC) at the Kendari City Regional General Hospital. The method used is descriptive cross-sectional. In this study, we collected data through the medical records of preeclampsia patients with sectio cesarea at the Kendari City Hospital in 2022 with 36 preeclampsia events. Mothers who are pregnant more than 3 times will experience excessive stretching of the uterus, causing preeclampsia. If someone has high parity, the reproductive system will decrease. Mother parity <2 or >4 times will be at risk of causing preeclampsia. All pregnant women are at risk of experiencing preeclampsia both in primigravidas and multigravidas. Based on the graph, the risk factors for preeclampsia in pregnant women are mostly experienced by productive age and more than 1 pregnancy (multipara), besides that it is also influenced by factors of low educational background , the mother's work as a housewife where there is a lack of information or education regarding risky pregnancies, as well as the presence of co-morbidities such as a history of Sectio Cesarea, Gemeli and previous history of hypertension, the incidence of pre-eclampsia at Kendari City Hospital in 2022 who is domiciled in Kendari City. Based on these data, it is hoped that the Kendari City Government can improve Health Promotion both through social media or in other health service settings as well as improve Health Services, especially for Pregnant Women who are both at risk and who are not at risk in order to reduce the incidence of Pre-eclampsia in Kendari City.